2016
DOI: 10.3109/10903127.2015.1128032
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Medical Services Utilization among Patients with ST-Segment Elevation Myocardial Infarction: Observations from the Singapore Myocardial Infarction Registry

Abstract: Less than half of STEMI patients utilized EMS and EMS patients had faster receipt of initial reperfusion therapies. Targeted public education to reduce time to treatment may improve the care of STEMI patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 28 publications
1
19
1
Order By: Relevance
“… 23 Moreover, ambulance transportation was used for only 19.4% of patients in provincial cities, 11.6% of patients in prefectures, and 12.0% of patients in counties, whereas 60% to 70% of patients in the US, Canada, the UK, and Japan and 50% of patients in Singapore use ambulances. 24 , 25 , 26 , 27 , 28 , 29 The possible reasons for this are thought to be mainly patients’ being unaware of their AMI and lack of information on EMSs’ performance. Furthermore, EMSs are still underdeveloped and inconvenient in China, especially in rural and remote areas.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Moreover, ambulance transportation was used for only 19.4% of patients in provincial cities, 11.6% of patients in prefectures, and 12.0% of patients in counties, whereas 60% to 70% of patients in the US, Canada, the UK, and Japan and 50% of patients in Singapore use ambulances. 24 , 25 , 26 , 27 , 28 , 29 The possible reasons for this are thought to be mainly patients’ being unaware of their AMI and lack of information on EMSs’ performance. Furthermore, EMSs are still underdeveloped and inconvenient in China, especially in rural and remote areas.…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies concluded that there was underutilization of EMS systems by ACS patients. [3][4][5] For those who experienced chest pain, early contact with health systems, particularly through prehospital medical providers, proved to have a beneficial role in revascularization following the cardiac ischemic event. 6 Multiple studies found that obtaining a pre-hospital electrocardiogram (ECG) will reduce the door-to-balloon time and lead to faster reperfusion therapy with a lower adjusted risk of mortality among ACS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Data from the Singapore Myocardial Infarction Registry included 4,667 patients with STEMI enrolled from 2010 to 2012 and showed that less than half of STEMI patients (49.8%) utilized EMS transport. Patients who used EMS transport were associated with higher rate of reperfusion therapy and resulted to shorter median symptom onset-to-balloon and door-to-balloon times [ 52 ]. The findings suggest that the STEMI network in Singapore should include programs that educate the community to call the ambulance/EMS using a unique phone number as a mode of transportation to a PCI center when a symptom of heart attack is suspected.…”
Section: Stemi Systems Of Care In Other Low-to-middle-income Countriementioning
confidence: 99%